Стратегиската улога на лидерството во развојот на организациското однесување - Нестороска Димиќ, Елизабета (Економски факултет, УКИМ, Скопје, 2013)
Leadership is one of the most important elements or features of modern management which occupies an increasingly important place in the economic literature. Successful leader is a person which by nature of things people follow him by their own choice, a person who is able to influence employees without the use of force and compulsion. The leader is a person who is able to lead employees (followers) to achieve more effective results and implement strategic organizational goals, with activation and full use of internal resources and the overall potential of the organization. At the same time, the leader has the capacity to recruit, develop and maintain top talents in the organization and that affects the creation and establishment of internal organizational environment that fosters, encourages and supports the creation of new leaders. In the phase of selection of the most effective leadership model, managers must never underestimate the role and importance of the informal organizational sybsystem, the so called ,,Shadows system” which for the first time defined by Stacey, used to explain number of less predictable, hidden and intangible aspects of organizational life among people, such as: values, attitudes and beliefs, leadership style and organizational behavior, organizational culture and norms of behavior, power, politics and conflicts, as well as numerous forms of informal organizational affiliation (Stacey, 2003). In the traditional organizations, it happens to never or almost never for these aspects to be discusses, but because these aspects of organizational life are somehow hidden, it does not mean that they do not exist. On the contrary, very often they tend to be crucial in the phase of making business decisions in the process of implementing organizational change and organizational transformation. The organizational culture and behavior in many organizations are crucial and determine the extent of transformations and changes in the organization, regardless of the challenges and requirements for change coming from the external environment. Regardless of how they are planned and how accurately and carefully changes in the organization are implemented by the formal subsystem, the informal subsystem is the one that enables, supports and implements or disables, stops or slows organizational success. Тhe organizational behavior and culture often tend to be the force that pulls towards, or the strength that provides strong resistance for the changes not to happen, not to be implemented in the desired direction or not to be realized with the expected intensity.
Strategic role of the leadership in developing of organizational behavior
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: leadership, leader, leadership style, organizational behavior, organizational culture, vision.